PERANAN WAKAF PRODUKTIF PEMUDA MUHAMMADIYAH UNTUK KESEJAHTERAAN WARGA DESA LONGKEYANG, BODEH, PEMALANG - Bakhri, Amirul (Jurnal Ekonomi Islam, 2017)
The one form of worship to be able closer to Allah SWT which is related to the property called a Waqf. Wakaf Istimari also called productive waqf, which is endowment wakaf used for investment, either in agriculture, industry, commerce, and services. This wakaf issue also developed in the village of Longkeyang, where the youth of Muhammadiyah Lokeyang tried to do wakaf for the welfare of the people. In the 2006, approximately 10 people from Muhammadiyah youth in Longkeyang together with activists of AMM (Muhammadiyah Youth Force) began a pioneer of the new institution (in 2010) which was named the Muhammadiyah Development Workersâ Development Agency (BP2RM). Some of the programs that have been generated from the management of productive endowments are waqfs of shrouds and scholarship for Muhammadiyah cadres.